2002
DOI: 10.1007/s10048-002-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel NF-L mutation Pro22Ser is associated with CMT2 in a large Slovenian family

Abstract: Charcot-Marie-Tooth (CMT) disease is the most-common form of inherited motor and sensory neuropathy. The autosomal dominant axonal form of the disease (CMT2) is currently subdivided into seven types based on genetic localization. These are CMT2A (1p35-p36), CMT2B (3q13-q22), CMT2C (unknown), CMT2D (7p14), CMT2E (8p21), HMNSP (3q13.1), and CMT2F (7q11-q21). Two loci have thus far been identified for autosomal recessive CMT2; ARCMT2A (1q21.1-q21.3) and ARCMT2B (19q13.3). Mutations in four genes (connexin 32, mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 20 publications
1
65
0
4
Order By: Relevance
“…1b). This mutation was found in the (Yoshihara et al 2002) and c.64C [ T resulting in Pro22Ser (Fabrizi et al 2004;Georgiou et al 2002), but this Pro22Arg mutation was not reported in the inherited peripheral neuropathies mutation database. Amino acids at the mutated site are highly conserved in different species (Fig.…”
Section: Molecular Genetic Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…1b). This mutation was found in the (Yoshihara et al 2002) and c.64C [ T resulting in Pro22Ser (Fabrizi et al 2004;Georgiou et al 2002), but this Pro22Arg mutation was not reported in the inherited peripheral neuropathies mutation database. Amino acids at the mutated site are highly conserved in different species (Fig.…”
Section: Molecular Genetic Analysismentioning
confidence: 96%
“…Particularly, two Pro22 mutations have been reported: Pro22Ser was found in CMT2E with giant axons in the sural nerve (Fabrizi et al 2004;Georgiou et al 2002), and Pro22Thr was found to be associated with CMT1F (Yoshihara et al 2002). It has been suggested that Pro22 mutations abolish the Thr-Pro phosphorylation sequence of the head domain of NEFL by proline-directed protein kinases (PDPKs) (Sasaki et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Linkage and haplotype analyses supported linkage of the mutation on the CMT2E locus and sequence analysis of the NFL gene revealed the corresponding mutations, as described by Georgiou et al (2002) and Zuchner et al (2004).…”
Section: Genetic Studiesmentioning
confidence: 71%
“…We studied two Slovenian families with an axonal autosomal dominant form of Charcot-Marie-Tooth disease caused by mutations in the NF-L gene. CMT2 in the family without AN is caused by the Pro22Ser (Georgiou et al, 2002) mutation and in NFL + AN family by the Glu397Lys (Zuchner et al, 2004) mutation. The genetic defects in these two families, occurring in the same gene, have different effects on auditory nerve, auditory brainstem, and central motor pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation